2009
DOI: 10.2527/jas.2008-1191
|View full text |Cite
|
Sign up to set email alerts
|

A whole genome scan for quantitative trait loci for leg weakness and its related traits in a large F2 intercross population between White Duroc and Erhualian1

Abstract: To detect QTL for leg weakness and its related traits in pigs, a total of 1,484 F 2 pigs were recorded for leg (at 76 and 213 d) and gait scores (at 153 and 223 d) in a White Duroc × Erhualian intercross. The length and weight of the biceps brachii muscle were measured after slaughter at 240 d. A genome scan was performed with 183 microsatellite markers in the population. A total of 42 QTL were detected, including 16 at the 1% genome-wide significant level and 6 at the 5% genome-wide significant level. Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 16 publications
6
19
0
1
Order By: Relevance
“…QTL for the same trait have been reported at 89 cM in a Landrace purebred [34] and at 52 cM in a Large White × Meishan intercross [20] on the same chromosome. The dominant QTL for FFS found on SSC16 at 36 cM is close to a previously reported dominant QTL at 27 cM for rear leg score [19]. The QTL identified for RLS on SSC6 and SSC18 are new and do not overlap with any previous study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…QTL for the same trait have been reported at 89 cM in a Landrace purebred [34] and at 52 cM in a Large White × Meishan intercross [20] on the same chromosome. The dominant QTL for FFS found on SSC16 at 36 cM is close to a previously reported dominant QTL at 27 cM for rear leg score [19]. The QTL identified for RLS on SSC6 and SSC18 are new and do not overlap with any previous study.…”
Section: Discussionsupporting
confidence: 81%
“…QTL analyses for leg weakness and bone-related traits have been performed in different pig breeds, including Landrace purebred [34], White Duroc × Erhualian [19,21], Large White × Meishan [20], Duroc × Landrace and Duroc × Large White crossbred [18], and Wild boar × Large White [17]. To the best of our knowledge, our study is the first to map QTL for LW-related traits in a Duroc and Pietrain intercross.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is supported by the findings of Fan et al (2009b), who found an association between body conformation traits and several genes controlling collagen structure, which is the main component of the connective tissue. For example, the COL1A2 gene, encoding the collagen α-2 chain protein, was found to be significantly associated with front and rear pasterns in pigs (Fan et al, 2009b) However, several other genomic studies have also been conducted to detect major genes related to structural soundness (Fan et al, 2009a(Fan et al, , 2009b(Fan et al, and 2011Guo et al, 2009), and multiple genes seem to be involved. For feet and leg structural soundness, for example, a clustering analysis showed that significant genes were involved in a variety of functions such as bone and cartilage development, muscle development and insulin regulations (Fan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondrosis (OC), often referred to as leg weakness, is a common problem in pig herds, it causes economic losses and is concerned of animal welfare in pig production (Jørgensen, 2000;Kadarmideen et al, 2004;Guo et al, 2009). The etiology and the pathogenesis of OC are not yet clarified but there are several factors associated with the changes in cartilaginous structures considered to cause OC.…”
Section: Introductionmentioning
confidence: 98%